Kedudukan Kuasa Allah dan Kuasa Manusia: Menurut Perspektif Al-Qur’an - Che Pa, Baharuddin (Jurnal Usuluddin, 2004)
This article aims to elucidate the difference between the concept of authority that belongs to Allah SWT the Lord of the worlds and the concept of authority that belongs to mankind as Allah s creatures. Allah SWT s authority cannot be compared with the kind of authority that mankind has. Allah SWT as the Omnipotent and All-Perfect Creator of mankind has an unlimited authority whereas mankind s sphere of authority, for obvious reasons, is limited. From the Islamic perspective, mankind is still bestowed with some authority, especially in the realm of jurisdiction on earth in keeping with mankind s status as the ennobled creature cum vicegerent of Allah SWT on earth. In this article, the difference between Allah s authority and mankind s authority will be laid out in great detail with references to Quranic verses as the ultimate source of jurisprudence in Islam.